Bismaleimide bridged silsesquioxane aerogels with excellent heat resistance: effect of sol–gel solvent polarity. Issue 14 (27th March 2020) - Zhao, Juan; Zeng, Guanjie; Zou, Fangxin; Jiang, Shaohua; Chen, Yeqing; Wang, Haiping; Mu, Chenzhong; Tang, Xiu-Zhi
Abstract : Bismaleimide bridged silsesquioxane aerogels with tailorable micro-structures exhibit superhydrophobicity, stable wettability, good compressive toughness, good thermal stability and thermal insulation. Abstract : Due to the poor heat-resistance and intrinsic weakness of the bridging moieties in aerogel matrixes, it remains greatly challenging to fabricate highly thermostable and toughened silsesquioxane aerogels. By utilizing bismaleimide as the bridging part and optimizing the solvent polarity, lightweight ( ρ < 0.09 g cm −3 ), compressible (80% strain) and superhydrophobic (CA ≈ 150°) bismaleimide bridged silsesquioxane aerogels (BMIT-BSAs) are constructed. The microstructure and compressive modulus of BMIT-BSAs can be tuned by the sol–gel solvents with different polarities. Moreover, stable low-temperature wettability at −196 °C and a significantly increased initial deposition temperature of 336 °C for both N2 and O2 atmospheres were measured, demonstrating the wide temperature tolerance of BMIT-BSAs.